(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Tambaru R, Burhanuddin AI, Massinai A, Amran MA. 2021. Detection of marine microalgae (phytoplankton) quality to support seafood health: a case study on the west coast of South Sulawesi, Indonesia. Biodiversitas 22: 5179- 5186. The research aimed to detect marine microalgae quality to support seafood health was carried out from January to November 2020 along the west coast of South Sulawesi, Indonesia. Samples were collected from the coastal waters of Pangkep District, Maros District, and the northern part of Makassar City. Phytoplankton cell counts were obtained using the deposition method developed by Uthermol. Phytoplankton cell abundances were calculated through sweeping (census) using a Sedgwick Rafter Cell (SRC). Two-way analysis of variance (ANOVA) was used to compare the distribution of marine microalgae community abundance between observation stations and periods. Based on the types and relative abundance of phytoplankton present, i.e., harmful algal bloom (HAB) forming or not (non-HAB), the results showed the quality of marine microalgae, specifically, phytoplankton was relatively good. Many more non-HAB (94-98%) than HAB (2-6%) marine microalgae were detected. Thus, the phytoplankton flourishing in these waters is mostly suitable as food for other organisms, including fish and shellfish. This also means that if fishers harvest these fish and shellfish, they should be fit and safe for human consumption.